Development of Cardiovascular Disease Therapeutics Using Space Environment: Opportunities and Challenges - Hyelim Park; Kyu-Sung Kim (Hanggong uju uihakoeji)
As research on the unique effects of space environment, especially microgravity and cosmic radiation, on the cardiovascular system is being conducted, research on the development of cardiovascular therapeutics using the space environment is attracting attention. This review comprehensively analyzes the current status and prospects of cardiovascular therapeutics development research utilizing space environment. Microgravity environment has been shown to have a positive effect on the proliferation and differentiation of cardiac progenitor cells and induced pluripotent stem cell-derived cardio myocytes. Cardiac tissue culture and organoid technology have enabled more effective drug screening and disease modeling than on the ground, and changes in gene expression such as Aquaporin-4 have been found to play an important role in cardiac function. Cosmic radiation can cause myocardial remodeling, fibrosis, and vascular endothelial dysfunction, and the underlying mechanisms of these effects include increased oxidative stress, promotion of inflammatory responses, deoxyribo nucleic acid damage, and cell death. Currently, the development of drugs that can prevent or treat cardiovascular damage caused by the space environment is in the early stages, and future research is expected to focus on developing personalized treatments and exploring the potential applications of space medicine research results to terrestrial medicine.